Role of Social Media and Digital Platforms in Healthcare Marketing: A Scoping Review - Wati, Dewi Kusuma; Sriatmi, Ayun; Arso, Septo Pawelas (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Healthcare providers face increased competition as they expand their facilities and services for patients. Healthcare marketing plays a significant role in their performance, with well-designed strategies resulting in better innovation outcomes and healthcare services. This scoping review analyzed how social media and digital platforms become part of the marketing strategy.Methods: This study employed a scoping review methodology to screen manuscripts from 4 databases: Proquest, Emerald Insight, Springerlink, and Garuda. PEO framework outlined as Population refers to healthcare consumers, Exposure was the digital marketing and Outcome was the effectiveness of social media and digital technologies in hospital. The eligibility criteria included: unrestricted access to the article, published in the last five years, manuscript in English.Results: PRISMA flow chart was used to show each step of the eligibility criteria for article selection. The study selected a total of 7 articles that met the inclusion criteria. Five of the articles showcased hospitals' social media strategies, one highlighted their adoption of social media, and one highlighted the impact of media framing. The social media had been found to positively affected both brand loyalty and the overall customer experience.Conclusion: The report emphasizes how social media and digital platforms are becoming more important in hospital marketing, as well as how they affect consumer satisfaction and brand loyalty.